Positive electrode material precursor, positive electrode material, preparation method and battery

By using functional additives in the preparation process of the precursor of the positive electrode material, the particle size distance is adjusted, and the problem of excessive diameter distance of the precursor of the large-particle positive electrode material is solved, and better cycle stability is achieved.

CN119528232APending Publication Date: 2025-02-28陕西红马科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411569177.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, the diameter distance of the precursor of the large-particle positive electrode material is relatively large, resulting in inconsistent problems in the process of preparing the positive electrode material, affecting the material performance.

Method used

During the preparation process of the precursor of large-particle positive electrode material, specific functional additives are used in the seed crystal stage, grain growth stage and post-treatment stage respectively to regulate the particle diameter distribution and achieve the narrowing of the particle diameter and Span value.

Benefits of technology

The diameter distance of the large-particle precursor is significantly narrowed, and the particle diameter distance Span value is 0.2-0.3, improving the cycle stability of the battery positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528232A_ABST
    Figure CN119528232A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, and discloses a positive electrode material precursor, a positive electrode material, a preparation method and a battery. The method comprises the following steps: (1) preparing raw materials including a first precipitator, a first complexing agent, a first auxiliary agent and water into a reaction base solution; (2) carrying out first coprecipitation reaction on the first metal salt solution, a second precipitator, a second complexing agent and the reaction base solution to obtain a first product system containing seed crystals; (3) carrying out second coprecipitation reaction on a second metal salt solution, a third precipitator, a third complexing agent, a second additive and the first product system to obtain a second product system; (4) washing the second product system with a solution containing a third auxiliary agent to obtain a positive electrode material precursor; and the D50 of the positive electrode material precursor is 10-18 [mu] m. Specific auxiliaries are used in different growth sections in the preparation process of the large-particle positive electrode material precursor, so that the span of the prepared precursor can be remarkably narrowed, and the cycling stability of the battery positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a positive electrode material precursor, a positive electrode material, a preparation method and a battery. Background Art

[0002] At present, the span value of the large particle precursor prepared by the intermittent method is generally in the range of 0.3-0.5. The large span of the precursor causes the small and medium particle precursors to enter the gaps in the large particle precursor. In the process of preparing positive electrode materials, due to the different sintering temperatures of large and small particles, there is inconsistency in the primary particles of the positive electrode material after sintering.

[0003] The main methods for narrowing the diameter of large particle precursors are: (1) by adjusting the preparation process parameters, such as the pH value of the synthesis system, the synthesis temperature, the concentration of the complexing agent, the precipitation agent and the dripping rate of the metal solution. (2) by adjusting the crystallization method, such as the multi-stage continuous overflow method, the multi-stage series intermittent method, the mother-child semi-continuous semi-intermittent method, etc. In the above methods, particles may be damaged, compacted or agglomerated during the filtering, washing and drying process, thereby affecting the particle size distribution of the precursor.

[0004] Therefore, it is urgent to develop new methods to narrow the diameter spacing of large-particle precursors in order to provide large-particle precursor products with narrower diameter spacing, which is of great significance for improving the performance of positive electrode materials. Summary of the invention

[0005] Aiming at the problem that existing positive electrode material precursors, especially large particle precursors, have large diameter distance, the present invention provides a positive electrode material precursor, a positive electrode material, a preparation method and a battery.

[0006] In order to achieve the above object, the present invention provides a method for preparing a positive electrode material precursor in a first aspect, the method comprising:

[0007] A method for preparing a positive electrode material precursor, characterized in that the method comprises:

[0008] (1) preparing a reaction base liquid by mixing raw materials including a first precipitant, a first complexing agent, a first auxiliary agent and water;

[0009] (2) subjecting the first metal salt solution, the second precipitant, the second complexing agent and the reaction base solution to a first coprecipitation reaction to obtain a first product system containing seed crystals;

[0010] (3) subjecting a second metal salt solution, a third precipitant, a third complexing agent, a second auxiliary agent and the first product system to a second coprecipitation reaction to obtain a second product system;

[0011] (4) washing the second product system with a solution containing a third auxiliary agent to obtain a positive electrode material precursor;

[0012] Wherein, the first auxiliary agent is selected from at least one of A salt, B salt, C salt and D salt; the second auxiliary agent is C salt; the third auxiliary agent is D salt;

[0013] The A salt is selected from at least one of sulfate, bisulfate and thiosulfate; the B salt is a sulfonate; the C salt is selected from chloride and / or hypochlorite; the D salt is selected from carbonate and / or bicarbonate;

[0014] The D50 of the positive electrode material precursor is 10-18 μm.

[0015] The second aspect of the present invention provides a positive electrode material precursor prepared by the method described in the first aspect.

[0016] The third aspect of the present invention provides a positive electrode material, which is obtained by sintering the positive electrode material precursor described in the second aspect and a lithium source or a sodium source.

[0017] A fourth aspect of the present invention provides a battery comprising the positive electrode material described in the third aspect.

[0018] The present invention uses specific functional additives in the seeding period, grain growth period and post-processing period of the large-particle positive electrode material precursor preparation process, which can significantly narrow the diameter of the large-particle precursor compared to the conventional preparation method, and achieve a particle diameter span value of 0.2-0.3. Furthermore, the positive electrode material precursor prepared by the method provided by the present invention is used to prepare the battery positive electrode material, which can make the battery positive electrode material have the advantage of good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0020] Figure 1 This is a SEM image of the positive electrode material precursor prepared in Preparation Example 1 of the present invention.

[0021] Figure 2 This is a SEM image of the positive electrode material precursor prepared in Comparative Preparation Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] A first aspect of the present invention provides a method for preparing a positive electrode material precursor, the method comprising:

[0024] (1) preparing a reaction base liquid by mixing raw materials including a first precipitant, a first complexing agent, a first auxiliary agent and water;

[0025] (2) subjecting the first metal salt solution, the second precipitant, the second complexing agent and the reaction base solution to a first coprecipitation reaction to obtain a first product system containing seed crystals;

[0026] (3) subjecting a second metal salt solution, a third precipitant, a third complexing agent, a second auxiliary agent and the first product system to a second coprecipitation reaction to obtain a second product system;

[0027] (4) washing the second product system with a solution containing a third auxiliary agent to obtain a positive electrode material precursor;

[0028] Wherein, the first auxiliary agent is selected from at least one of A salt, B salt, C salt and D salt; the second auxiliary agent is C salt; the third auxiliary agent is D salt;

[0029] The A salt is selected from at least one of sulfate, bisulfate and thiosulfate; the B salt is a sulfonate; the C salt is selected from chloride and / or hypochlorite; the D salt is selected from carbonate and / or bicarbonate;

[0030] The D50 of the positive electrode material precursor is 10-18 μm.

[0031] The inventors of the present invention have found in their research that in the preparation process of large-particle precursors (D50 is 10-18μm), by using specific functional additives in different preparation stages, the diameter distance of large-particle precursors can be narrowed. Specifically, in the seed stage, the introduction of the first additive in the reaction base liquid can enhance the repulsion between small-particle crystals (D50≤6μm) and avoid the agglomeration of small particles in the seed stage; the addition of the second additive in the grain growth stage (6μm<D50≤18μm) can enhance the complexing ability of large-particle crystals, make the surface regular, and not easy to gather new small particles; in the post-processing stage, the third additive can inhibit the shedding of micropowder from the surface of large particles during washing. Under the joint action of the additives in the above three stages, the diameter distance of the large-particle precursor product can be significantly narrowed, and the particle diameter distance Span value can be achieved to be 0.2-0.3, thereby significantly improving the cycle stability of the battery positive electrode material.

[0032] In the present invention, the particle size (D50) of the positive electrode material precursor or the intermediate product of the positive electrode material precursor during the preparation process is measured by a laser particle size analyzer.

[0033] In the present invention, the particle size span value refers to the concentration of the particle size distribution, which can be calculated by the formula Span = (D90-D10) / D50.

[0034] According to the present invention, in the method for preparing the cathode material precursor, preferably, the A salt is selected from at least one of sodium sulfate, ammonium sulfate, ammonium hydrogen sulfate and sodium thiosulfate.

[0035] According to the present invention, further preferably, the A salt is sodium sulfate.

[0036] According to the present invention, in the method for preparing the positive electrode material precursor, preferably, the B salt is sodium sulfonate.

[0037] According to the present invention, in the method for preparing the cathode material precursor, preferably, the C salt is selected from at least one of sodium chloride, ammonium chloride and sodium hypochlorite.

[0038] According to the present invention, further preferably, the C salt is sodium chloride.

[0039] According to the present invention, in the method for preparing the positive electrode material precursor, preferably, the D salt is selected from at least one of sodium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate.

[0040] According to the present invention, further preferably, the D salt is sodium carbonate.

[0041] According to the present invention, in the method for preparing the positive electrode material precursor, the first precipitant, the second precipitant, and the third precipitant are relatively broad and can be selected conventionally in the art. Preferably, the first precipitant, the second precipitant, and the third precipitant are each independently selected from at least one of sodium hydroxide, sodium carbonate, and sodium bicarbonate, and more preferably sodium hydroxide.

[0042] In the present invention, the materials of the first precipitant, the second precipitant and the third precipitant may be the same or different, and preferably the three are the same.

[0043] Preferably, the first precipitant, the second precipitant and the third precipitant are all sodium hydroxide.

[0044] According to the present invention, in the method for preparing the positive electrode material precursor, the restriction on the complexing agent is relatively broad, and conventional selections in the art can be adopted. Preferably, the first complexing agent, the second complexing agent and the third complexing agent are all ammonia water.

[0045] According to the present invention, in the method for preparing the positive electrode material precursor, the metal salts in the first metal salt solution and the second metal salt solution are the same. The metal salts in the first metal salt solution and the second metal salt solution can each independently include a metal salt and b metal salt; wherein the a metal salt is a nickel salt, and the b metal salt is selected from a manganese salt and / or a salt containing an element M; wherein the element M can be selected from at least one of Co, Al, Fe, Zn, Cr, Ti and Mg.

[0046] In the present invention, for the metal salts in the first metal salt solution and the second metal salt solution, the molar ratio of a metal salt calculated as element Ni: b metal salt calculated as element Mn and / or element M is (25-98): (1-80) independently of each other. In the above ratio, when the b metal salt is all manganese salt, the amount of the b metal salt is calculated as the amount of element Mn; when the b metal salt is all salt containing element M, the amount of the b metal salt is calculated as the amount of element M; when the b metal salt includes both manganese salt and salt containing element M, the amount of the b metal salt is calculated as the sum of the amounts of element Mn and element M.

[0047] According to the present invention, the metal salt in the first metal salt solution and the second metal salt solution can be at least one of sulfate, carbonate, oxalate, acetate and chloride, preferably sulfate.

[0048] According to the present invention, in the method for preparing the positive electrode material precursor, the first metal salt solution and the second metal salt solution are aqueous solutions of the above-mentioned metal salts.

[0049] According to the present invention, in the method for preparing the positive electrode material precursor, in step (1), there is no particular limitation on the order of feeding the raw materials, as long as the raw materials can be fully mixed to obtain a uniform and stable reaction base liquid. According to a preferred embodiment of the present invention, the reaction base liquid can be prepared in the following manner:

[0050] The first auxiliary agent, the first precipitant and the first complexing agent are sequentially added into the water, and the mixture is fully stirred and mixed to obtain the uniform and stable reaction base liquid.

[0051] According to the present invention, in step (1), preferably, the amount of the first precipitant added is such that the pH value of the reaction bottom liquid is 10-13.

[0052] According to the present invention, in step (1), preferably, the feeding amount of the first complexing agent is such that, in the reaction base solution, the concentration of the first complexing agent (in terms of NH3) is 1-12 g / L.

[0053] According to the present invention, in step (1), preferably, the feeding amount of the first auxiliary agent is such that, in the reaction base solution, the concentration of the first auxiliary agent (in terms of salt) is 0.05-0.15 g / L.

[0054] According to the present invention, in step (1), preferably, the volume of the reaction base liquid accounts for 50-80% of the volume of the reaction kettle used for the coprecipitation reaction.

[0055] According to a preferred embodiment of the present invention, in step (1), the first auxiliary agent is selected from salt A and / or salt B. When the first auxiliary agent is salt A and / or salt B, compared with the case where the first auxiliary agent is salt C and / or salt D, it is more conducive to improving the dispersibility of small particles in the seed stage, and provides a basis for narrowing the diameter distance in the large particle growth stage.

[0056] According to the present invention, in step (2), preferably, the first metal salt solution, the second precipitant and the second complexing agent are continuously introduced into the reaction base solution prepared in step (1), and the feed flow rate is adjusted according to the requirements of the reaction conditions to carry out the first co-precipitation reaction.

[0057] According to the present invention, preferably, the conditions of the first coprecipitation reaction include: the temperature of the reaction system is 40-80°C, the pH value of the reaction system is 10-13, and the concentration of the complexing agent in the reaction system is 1-12 g / L. The concentration of the complexing agent in the reaction system refers to the total concentration of the first complexing agent (from the reaction base solution) present in the reaction system and the second complexing agent added in step (2).

[0058] According to the present invention, preferably, the concentration of the metal salt (based on the total molar concentration of metal cations) in the first metal salt solution is 1-3 mol / L. During the first coprecipitation reaction, preferably, the volume flow rate of the first metal salt solution fed per hour is 1-10% of the volume of the reactor used for the coprecipitation reaction.

[0059] According to the present invention, in step (2), preferably, the second precipitant and the second complexing agent are each fed in the form of an aqueous solution. Preferably, the concentration of the aqueous solution of the second precipitant is 5-11 mol / L; the concentration of the aqueous solution of the second complexing agent (when the second complexing agent is ammonia water, it refers to the concentration calculated as NH3) is 6-10 mol / L.

[0060] According to the present invention, in step (2), the feed flow rate of the second precipitant is such that the pH value of the reaction system is maintained at 10-13; the feed flow rate of the second complexing agent is such that the concentration of the complexing agent in the reaction system is maintained at 1-12 g / L.

[0061] According to the present invention, in step (2), the D50 of the seed crystal is 1-6 μm. When the solid phase particles (seed crystals) in the first product system formed by the first coprecipitation reaction are measured to reach the above-mentioned particle size range, it can be considered that the seed crystal stage in the preparation method of the present invention is completed, and the grain growth stage can be carried out next.

[0062] According to the present invention, in step (3), preferably, the second auxiliary agent, the second metal salt solution, the third precipitant and the third complexing agent are continuously introduced into the first product system obtained in step (2), and the feed flow rate is adjusted according to the requirements of the reaction conditions to carry out the second co-precipitation reaction.

[0063] According to the present invention, preferably, the conditions of the second coprecipitation reaction include: the temperature of the reaction system is 40-80°C, the pH value of the reaction system is 10-13, and the concentration of the complexing agent in the reaction system is 1-12g / L. The concentration of the complexing agent in the reaction system refers to the total concentration of the first complexing agent (from the reaction base liquid) present in the reaction system, the second complexing agent added in step (2), and the third complexing agent added in step (3).

[0064] According to the present invention, in step (3), preferably, the concentration of the metal salt (based on the total molar concentration of metal cations) in the second metal salt solution is 1-3 mol / L. During the second coprecipitation reaction, preferably, the volume flow rate of the second metal salt solution per hour is 1-10% of the volume of the reactor used for the coprecipitation reaction.

[0065] According to the present invention, in step (3), preferably, the feeding amount of the second auxiliary agent is such that the concentration of the second auxiliary agent in the reaction system is 0.02-0.15 mol / L, which is beneficial to enhance the complexing ability of large particles, make the particle surface regular, and not easy to aggregate the newly added small balls, thereby achieving the purpose of narrowing the diameter distance.

[0066] According to the present invention, in step (3), preferably, the third precipitant and the third complexing agent are each fed in the form of an aqueous solution. Preferably, the concentration of the aqueous solution of the third precipitant is 5-11 mol / L; the concentration of the aqueous solution of the third complexing agent (when the third complexing agent is ammonia water, it refers to the concentration calculated as NH3) is 6-10 mol / L.

[0067] According to the present invention, in step (3), the feed flow rate of the third precipitant is such that the pH value of the reaction system is maintained at 10-13; the feed flow rate of the third complexing agent is such that the concentration of the complexing agent in the reaction system is maintained at 1-12 g / L.

[0068] According to the present invention, preferably, the first coprecipitation reaction and the second coprecipitation reaction are both carried out under a protective atmosphere, such as a nitrogen atmosphere, a helium atmosphere, a neon atmosphere, an argon atmosphere, and the like.

[0069] According to the present invention, in step (3), when it is measured that the solid phase particles in the second product system formed by the second coprecipitation reaction reach the target particle size, the feeding is stopped and the second coprecipitation reaction is terminated.

[0070] According to the present invention, in step (4), preferably, in the solution containing the third auxiliary agent, the concentration of the third auxiliary agent is 0.05-0.2 mol / L, which helps to prevent the shedding of micropowder from the surface of large particles during washing, thereby increasing the number of small balls and causing the particle size distribution of the product to become wider.

[0071] According to the present invention, in step (4), the solid phase in the second product system is separated and washed. Preferably, the washing conditions include: a temperature of 40-60° C. and a time of 0.5-2 h.

[0072] According to the present invention, the preparation method further comprises drying and sieving the washed product to finally obtain a positive electrode material precursor.

[0073] By adopting the preparation method provided by the present invention, the diameter span of the large-particle precursor product can be significantly narrowed, and the obtained precursor particle diameter span value is 0.2-0.3. The large-particle positive electrode material precursor prepared by this method is used to prepare the positive electrode material, which can make the positive electrode material have better cycle stability than the large-particle positive electrode material precursor prepared by the conventional method (under the premise of the same or similar particle size).

[0074] The second aspect of the present invention provides a positive electrode material precursor prepared by the method described in the first aspect.

[0075] The positive electrode material precursor provided by the present invention has a D50 of 10-18 μm, which is a large particle precursor in terms of particle size, and has the characteristic of small particle diameter span, with a particle diameter span value of 0.2-0.3. The positive electrode material prepared by the precursor can have the performance advantage of good cycle stability.

[0076] According to the present invention, preferably, the chemical composition of the positive electrode material precursor satisfies the chemical formula (Ni x Mn y M z )(OH)2, wherein 0.25≤x≤0.98, 0≤y≤0.80, 0≤z≤0.80, y and z are not 0 at the same time, and x+y+z=1; the element M is selected from at least one of Co, Al, Fe, Zn, Cr, Ti and Mg.

[0077] The third aspect of the present invention provides a positive electrode material, which is obtained by sintering the positive electrode material precursor described in the second aspect and a lithium source or a sodium source.

[0078] According to the present invention, the positive electrode material for a lithium-ion battery can be prepared by sintering the positive electrode material precursor and a lithium source together.

[0079] In the present invention, the lithium source is relatively broad, and any lithium source that can be used to prepare positive electrode materials for lithium-ion batteries can be used. Preferably, the lithium source is lithium hydroxide and / or lithium carbonate.

[0080] According to the present invention, when the cathode material precursor and the lithium source are sintered together, preferably, the molar ratio of the cathode material precursor: the lithium source is 1:(1.01-1.1). Preferably, the sintering conditions include: a temperature of 500-950°C and a time of 8-20h.

[0081] According to the present invention, a sodium ion battery positive electrode material can be prepared by sintering the positive electrode material precursor and a sodium source together.

[0082] In the present invention, the sodium source is relatively broad, and any lithium source that can be used to prepare anode materials for sodium ion batteries can be used. Preferably, the sodium source is sodium carbonate.

[0083] In the present invention, when the cathode material precursor and the sodium source are sintered together, preferably, the molar ratio of the cathode material precursor: the sodium source is 1:(1.01-1.25). Preferably, the sintering is carried out in two stages, and the sintering conditions include: the temperature of the first stage sintering is 500-800°C, and the time is 4-10h; the temperature of the second stage sintering is 800-1100°C, and the time is 6-15h.

[0084] In the present invention, sintering is preferably performed in an oxygen or air atmosphere.

[0085] The positive electrode material provided by the present invention is obtained by sintering the positive electrode material precursor described in the second aspect above with a lithium source or a sodium source. The particle diameter of the positive electrode material precursor is small, which is conducive to shortening the sintering time. The grain size consistency formed by sintering is good, and the diffusion rate of lithium ions or sodium ions during the sintering process is almost the same. The obtained positive electrode material has the performance advantage of good cycle stability.

[0086] A fourth aspect of the present invention provides a battery comprising the positive electrode material described in the third aspect.

[0087] The battery provided by the present invention adopts the positive electrode material provided by the present invention, so that the battery has the performance advantage of good cycle stability.

[0088] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0089] Preparation Example 1

[0090] Seeding stage:

[0091] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 60° C., and then sodium sulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0092] The pH value of the reaction bottom liquid is 11.7, wherein the concentration of sodium sulfate is 0.08 g / L, and the content of ammonia (in terms of NH3) is 4.0 g / L; the volume of the reaction bottom liquid accounts for 62% of the volume of the reactor;

[0093] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 80:10:10 and the total concentration of metal cations is 2 mol / L), a NaOH aqueous solution (concentration of 10 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 60° C.), wherein the flow rate of the metal salt solution is 30 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the ammonia content (in terms of NH3) in the reaction system is 3.5-4.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 800 rpm;

[0094] When the particle size D50 of the solid phase material in the reactor reaches 4.5 μm, the seeding stage ends;

[0095] Growth stage:

[0096] (3) continuously introducing sodium chloride, the metal salt solution, NaOH aqueous solution (concentration of 10 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature is 60° C.), wherein the flow rate of the metal salt solution is 30 L / h, the pH value of the reaction system is maintained at 11.0-11.5, the sodium chloride content in the reaction system is 0.02 mol / L, the ammonia content (as NH3) in the reaction system is 4.5-5.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 600 rpm;

[0097] When the particle size D50 of the solid phase material in the reactor reaches 10.56 μm, the feeding is stopped;

[0098] Post-processing stage:

[0099] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous sodium carbonate solution (concentration of 0.05 mol / L) at a washing temperature of 60° C. for 0.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q1).

[0100] The D50 of Q1 is 10.56μm, the span value is 0.28, and the chemical composition satisfies the chemical formula (Ni 0.80 Co 0.10 Mn 0.10 )(OH)2.

[0101] The results of the SEM test on Q1 are as follows: Figure 1 As shown, it can be seen that there are no small balls or medium balls in the Q1 particles, and the particle distribution consistency is good.

[0102] Preparation Example 2

[0103] Seeding stage:

[0104] (1) In a volume of 1m 3 In a reaction kettle, first add 700 L of pure water, heat to 40°C, then add sodium thiosulfate, NaOH aqueous solution and ammonia water in sequence, stir and mix thoroughly to obtain a reaction base liquid;

[0105] The pH value of the reaction bottom liquid is 12.8, wherein the concentration of sodium thiosulfate is 0.05 g / L, and the content of ammonia (in terms of NH3) is 9.5 g / L; the volume of the reaction bottom liquid accounts for 74% of the volume of the reactor;

[0106] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate and cobalt sulfate, wherein the molar ratio of Ni:Co is 90:10 and the total concentration of metal cations is 1.5 mol / L), a NaOH aqueous solution (concentration is 8 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 40° C.), wherein the flow rate of the metal salt solution is 25 L / h, the pH value of the reaction system is maintained at 12.5-13.0, the ammonia (as NH3) content in the reaction system is 9-10 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 700 rpm;

[0107] When the particle size D50 of the solid phase material in the reactor reaches 5.5 μm, the seeding stage ends;

[0108] Growth stage:

[0109] (3) continuously introducing ammonium chloride, the metal salt solution, the NaOH aqueous solution (concentration of 8 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature is 40° C.), wherein the flow rate of the metal salt mixed solution is 25 L / h, the pH value of the reaction system is maintained at 12.0-12.5, the ammonium chloride content in the reaction system is 0.05 mol / L, the ammonia content (as NH3) in the reaction system is 10-11 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 500 rpm;

[0110] When the particle size D50 of the solid phase material in the reactor reaches 13.49 μm, the feeding is stopped;

[0111] Post-processing stage:

[0112] (4) The solid phase in the product system obtained in step (3) is separated and washed with an aqueous sodium bicarbonate solution (concentration of 0.08 mol / L) at a washing temperature of 40° C. for 2 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q2).

[0113] The D50 of Q2 is 13.49 μm, the span value is 0.26, and the chemical composition satisfies the chemical formula (Ni 0.90 Co 0.10 )(OH)2.

[0114] Preparation Example 3

[0115] Seeding stage:

[0116] (1) In a volume of 1m 3 In a reaction kettle, 500 L of pure water was first added, the temperature was raised to 70° C., and then sodium sulfonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0117] The pH value of the reaction bottom liquid is 11.7, wherein the concentration of sodium sulfonate is 0.10 g / L, and the content of ammonia (in terms of NH3) is 8 g / L; the volume of the reaction bottom liquid accounts for 52% of the volume of the reactor;

[0118] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 40:20:40 and the total concentration of metal cations is 3.0 mol / L), a NaOH aqueous solution (concentration is 5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 70° C.), wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the ammonia (as NH3) content in the reaction system is 7.5-8.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 600 rpm;

[0119] When the particle size D50 of the solid phase material in the reactor reaches 5.89 μm, the seeding stage ends;

[0120] Growth stage:

[0121] (3) continuously introducing sodium chloride, the metal salt mixed solution, NaOH aqueous solution (concentration of 5 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature is 70° C.), wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 11.0-12.0, the sodium chloride content in the reaction system is 0.15 mol / L, the ammonia content (as NH3) in the reaction system is 6.5-7.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 300 rpm;

[0122] When the particle size D50 of the solid phase material in the reactor reaches 12.40 μm, the feeding is stopped;

[0123] Post-processing stage:

[0124] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous ammonium carbonate solution (concentration of 0.12 mol / L) at a washing temperature of 60° C. for 1.8 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q3).

[0125] The D50 of Q3 is 12.40 μm, the span value is 0.24, and the chemical composition satisfies the chemical formula (Ni 0.40 Fe 0.20 Mn 0.40 )(OH)2.

[0126] Preparation Example 4

[0127] Seeding stage:

[0128] (1) In a volume of 1m 3 In a reaction kettle, first add 750L of pure water, heat to 80°C, then add ammonium hydrogen sulfate, NaOH aqueous solution and ammonia water in sequence, stir and mix thoroughly to obtain a reaction bottom liquid;

[0129] The pH value of the reaction bottom liquid is 12.1, wherein the concentration of ammonium bisulfate is 0.12 g / L, and the ammonia (in terms of NH3) content is 1.5 g / L; the volume of the reaction bottom liquid accounts for 76% of the volume of the reactor;

[0130] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 60:20:20 and the total concentration of metal cations is 1.0 mol / L), a NaOH aqueous solution (concentration is 6 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 80° C.), wherein the flow rate of the metal salt solution is 20 L / h, the pH value of the reaction system is maintained at 11.8-12.4, the ammonia content (in terms of NH3) in the reaction system is 1.0-2.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 650 rpm;

[0131] When the particle size D50 of the solid phase material in the reactor reaches 5.94 μm, the seeding stage ends;

[0132] Growth stage:

[0133] (3) Sodium hypochlorite, the metal salt mixed solution, NaOH aqueous solution (concentration of 6 mol / L) and ammonia water (concentration of 8 mol / L) were continuously introduced into the above reactor, and a second coprecipitation reaction was carried out under nitrogen atmosphere and stirring conditions (reaction temperature was 80° C.), wherein the flow rate of the metal salt solution was 20 L / h, the pH value of the reaction system was maintained at 11.4-12.0, the content of sodium hypochlorite in the reaction system was 0.10 mol / L, the content of ammonia (as NH3) in the reaction system was 1.0-2.0 g / L, the nitrogen flow rate was 500 L / h, and the stirring speed was 450 rpm;

[0134] When the particle size D50 of the solid phase material in the reactor reaches 15.48 μm, the feeding is stopped;

[0135] Post-processing stage:

[0136] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous solution of ammonium bicarbonate (concentration of 0.10 mol / L) at a washing temperature of 50° C. for 1.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q4).

[0137] The D50 of Q4 is 15.48μm, the span value is 0.25, and the chemical composition satisfies the chemical formula (Ni 0.60 Co 0.20 Mn 0.20 )(OH)2.

[0138] Preparation Example 5

[0139] Seeding stage:

[0140] (1) In a volume of 1m 3In a reaction kettle, 650 L of pure water was first added, the temperature was raised to 50° C., and then ammonium sulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0141] The pH value of the reaction bottom liquid is 10.8, wherein the concentration of ammonium sulfate is 0.10 g / L, and the ammonia (in terms of NH3) content is 2.7 g / L; the volume of the reaction bottom liquid accounts for 66% of the volume of the reactor;

[0142] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, manganese sulfate, iron sulfate and zinc sulfate, wherein the molar ratio of Ni:Mn:Fe:Zn is 32:30:30:8 and the total concentration of metal salt cations is 1.2 mol / L), a NaOH aqueous solution (concentration of 11 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 50° C.), wherein the flow rate of the metal salt solution is 10 L / h, the pH value of the reaction system is maintained at 10.5-11.0, the ammonia content (in terms of NH3) in the reaction system is 2.5-3.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 400 rpm;

[0143] When the particle size D50 of the solid phase material in the reactor reaches 5.43 μm, the seeding stage ends;

[0144] Growth stage:

[0145] (3) continuously introducing ammonium chloride, the metal salt solution, the NaOH aqueous solution (with a concentration of 11 mol / L) and ammonia water (with a concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a second coprecipitation reaction (reaction temperature is 50° C.) under nitrogen atmosphere and stirring conditions, wherein the flow rate of the metal salt solution is 10 L / h, the pH value of the reaction system is maintained at 10.0-10.8, the ammonium chloride content in the reaction system is 0.08 mol / L, the ammonia content (as NH3) in the reaction system is 2.5-3.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 300 rpm;

[0146] When the particle size D50 of the solid phase material in the reactor reaches 17.63 μm, the feeding is stopped;

[0147] Post-processing stage:

[0148] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous sodium carbonate solution (concentration of 0.10 mol / L) at a washing temperature of 45° C. for 1.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q5).

[0149] The D50 of Q5 is 17.63μm, the span value is 0.29, and the chemical composition satisfies the chemical formula (Ni 0.32 Fe 0.30 Mn 0.30 Zn 0.08 )(OH)2.

[0150] Preparation Example 6

[0151] Seeding stage:

[0152] (1) In a volume of 1m 3 In a reaction kettle, 550 L of pure water was first added, the temperature was raised to 55° C., and then sodium sulfonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0153] The pH value of the reaction bottom liquid is 12.2, wherein the concentration of sodium sulfonate is 0.13 g / L, and the content of ammonia (in terms of NH3) is 5.5 g / L; the volume of the reaction bottom liquid accounts for 57% of the volume of the reactor;

[0154] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 95:3:2 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 7 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 55° C.), wherein the flow rate of the metal salt solution is 40 L / h, the pH value of the reaction system is maintained at 11.8-12.5, the ammonia content (in terms of NH3) in the reaction system is 5.0-6.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 550 rpm;

[0155] When the particle size D50 of the solid phase material in the reactor reaches 5.86 μm, the seeding stage ends;

[0156] Growth stage:

[0157] (3) Sodium hypochlorite, the metal salt solution, NaOH aqueous solution (concentration of 7 mol / L) and ammonia water (concentration of 8 mol / L) were continuously introduced into the reactor to carry out a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature was 55° C.), wherein the flow rate of the metal salt solution was 40 L / h, the pH value of the reaction system was maintained at 11.5-12.0, the content of sodium hypochlorite in the reaction system was 0.06 mol / L, the content of ammonia (as NH3) in the reaction system was 5.0-6.0 g / L, the nitrogen flow rate was 500 L / h, and the stirring speed was 350 rpm;

[0158] When the particle size D50 of the solid phase material in the reactor reaches 14.69 μm, the feeding is stopped;

[0159] Post-processing stage:

[0160] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous sodium bicarbonate solution (concentration of 0.15 mol / L) at a washing temperature of 50° C. for 1.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q6).

[0161] The D50 of Q6 is 14.69μm, the span value is 0.22, and the chemical composition satisfies the chemical formula (Ni 0.95 Co 0.03 Mn 0.02 )(OH)2.

[0162] Preparation Example 7

[0163] Seeding stage:

[0164] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 65°C, and then sodium thiosulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0165] The pH value of the reaction bottom liquid is 11.2, wherein the concentration of sodium thiosulfate is 0.15 g / L, and the content of ammonia (in terms of NH3) is 9 g / L; the volume of the reaction bottom liquid accounts for 63% of the volume of the reactor;

[0166] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 29:30:41 and the total concentration of metal cations is 1.8 mol / L), a NaOH aqueous solution (concentration is 9 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 65° C.), wherein the flow rate of the metal salt solution is 45 L / h, the pH value of the reaction system is maintained at 10.8-11.5, the ammonia content (in terms of NH3) in the reaction system is 8.5-9.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 500 rpm;

[0167] When the particle size D50 of the solid phase material in the reactor reaches 5.29 μm, the seeding stage ends;

[0168] Growth stage:

[0169] (3) continuously introducing sodium chloride, the metal salt solution, NaOH aqueous solution (concentration of 9 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature is 65° C.), wherein the flow rate of the metal salt solution is 45 L / h, the pH value of the reaction system is maintained at 10.5-11.0, the sodium chloride content in the reaction system is 0.12 mol / L, the ammonia content (as NH3) in the reaction system is 8.5-9.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 300 rpm;

[0170] When the particle size D50 of the solid phase material in the reactor reaches 13.80 μm, the feeding is stopped;

[0171] Post-processing stage:

[0172] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous solution of ammonium bicarbonate (concentration of 0.18 mol / L) at a washing temperature of 60° C. for 1.8 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q7).

[0173] The D50 of Q7 is 13.80μm, the span value is 0.27, and the chemical composition satisfies the chemical formula (Ni 0.29 Fe 0.30 Mn 0.41 )(OH)2.

[0174] Preparation Example 8

[0175] Seeding stage:

[0176] (1) In a volume of 1m 3 In a reaction kettle, 640 L of pure water was first added, the temperature was raised to 75°C, and then sodium thiosulfate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0177] The pH value of the reaction bottom liquid is 12.3, wherein the concentration of sodium thiosulfate is 0.05 g / L, and the ammonia (in terms of NH3) content is 11.5 g / L; the volume of the reaction bottom liquid accounts for 69% of the volume of the reactor;

[0178] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 50:20:30 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 10.5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 75° C.), wherein the flow rate of the metal salt solution is 50 L / h, the pH value of the reaction system is maintained at 11.8-12.5, the ammonia content (in terms of NH3) in the reaction system is 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 400 rpm;

[0179] When the particle size D50 of the solid phase material in the reactor reaches 5.46 μm, the seeding stage ends;

[0180] Growth stage:

[0181] (3) continuously introducing sodium chloride, the metal salt mixed solution, NaOH aqueous solution (concentration of 10.5 mol / L) and ammonia water (concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature is 75° C.), wherein the flow rate of the metal salt solution is 50 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the sodium chloride content in the reaction system is 0.03 mol / L, the ammonia content (as NH3) in the reaction system is 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 200 rpm;

[0182] When the particle size D50 of the solid phase material in the reactor reaches 15.20 μm, the feeding is stopped;

[0183] Post-processing stage:

[0184] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous sodium carbonate solution (concentration of 0.20 mol / L) at a washing temperature of 50° C. for 1.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q8).

[0185] The D50 of Q8 is 15.20 μm, the span value is 0.28, and the chemical composition satisfies the chemical formula (Ni 0.50 Fe 0.20 Mn 0.30 )(OH)2.

[0186] Preparation Example 9

[0187] Seeding stage:

[0188] (1) In a volume of 1m 3In a reaction kettle, 640 L of pure water was first added, the temperature was raised to 75°C, and then ammonium chloride, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0189] The pH value of the reaction bottom liquid is 12.3, wherein the concentration of ammonium chloride is 0.05 g / L, and the content of ammonia (in terms of NH3) is 11.5 g / L; the volume of the reaction bottom liquid accounts for 69% of the volume of the reactor;

[0190] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 50:20:30 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 10.5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 75° C.), wherein the flow rate of the metal salt solution is 50 L / h, the pH value of the reaction system is maintained at 11.8-12.5, the ammonia content (in terms of NH3) in the reaction system is 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 400 rpm;

[0191] When the particle size D50 of the solid phase material in the reactor reaches 5.40 μm, the seeding stage ends;

[0192] Growth stage:

[0193] (3) continuously introducing sodium chloride, the metal salt mixed solution, NaOH aqueous solution (concentration of 10.5 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature of 75° C.), wherein the flow rate of the metal salt mixed solution is 50 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the sodium chloride content in the reaction system is 0.03 mol / L, the ammonia content (as NH3) in the reaction system is 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 200 rpm;

[0194] When the particle size D50 of the solid phase material in the reactor reaches 15.23 μm, the feeding is stopped;

[0195] Post-processing stage:

[0196] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous sodium carbonate solution (concentration of 0.20 mol / L) at a washing temperature of 50° C. for 1.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q9).

[0197] The D50 of Q9 is 15.23 μm, the span value is 0.30, and the chemical composition satisfies the chemical formula (Ni 0.50 Fe 0.20 Mn 0.30 )(OH)2.

[0198] Preparation Example 10

[0199] Seeding stage:

[0200] (1) In a volume of 1m 3 In a reaction kettle, 640 L of pure water was first added, the temperature was raised to 75°C, and then sodium carbonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0201] The pH value of the reaction bottom liquid is 12.3, wherein the concentration of sodium carbonate is 0.05 g / L, and the content of ammonia (in terms of NH3) is 11.5 g / L; the volume of the reaction bottom liquid accounts for 69% of the volume of the reactor;

[0202] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 50:20:30 and the total concentration of metal cations is 2.5 mol / L), a NaOH aqueous solution (concentration is 10.5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 75° C.), wherein the flow rate of the metal salt solution is 50 L / h, the pH value of the reaction system is maintained at 11.8-12.5, the ammonia content (in terms of NH3) in the reaction system is 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 400 rpm;

[0203] When the particle size D50 of the solid phase material in the reactor reaches 5.52 μm, the seeding stage ends;

[0204] Growth stage:

[0205] (3) continuously introducing sodium chloride, the metal salt mixed solution, NaOH aqueous solution (concentration of 10.5 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature of 75° C.), wherein the flow rate of the metal salt mixed solution is 50 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the sodium chloride content in the reaction system is 0.03 mol / L, the ammonia content (as NH3) in the reaction system is 11.0-12.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 200 rpm;

[0206] When the particle size D50 of the solid phase material in the reactor reaches 15.22 μm, the feeding is stopped;

[0207] Post-processing stage:

[0208] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous sodium carbonate solution (concentration of 0.20 mol / L) at a washing temperature of 50° C. for 1.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as Q10).

[0209] The D50 of Q10 is 15.22μm, the span value is 0.29, and the chemical composition satisfies the chemical formula (Ni 0.50 Fe 0.20 Mn 0.30 )(OH)2.

[0210] Comparative Preparation Example 1

[0211] Seeding stage:

[0212] (1) In a volume of 1m 3 In a reaction kettle, 600 L of pure water was first added, the temperature was raised to 60°C, and then NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0213] The pH value of the reaction bottom liquid is 11.7, wherein the ammonia (in terms of NH3) content is 4.0 g / L; the volume of the reaction bottom liquid accounts for 62% of the volume of the reactor;

[0214] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate, wherein the molar ratio of Ni:Co:Mn is 80:10:10 and the total concentration of metal cations is 2 mol / L), a NaOH aqueous solution (concentration of 10 mol / L) and an ammonia solution (concentration of 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 60° C.), wherein the flow rate of the metal salt solution is 30 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the ammonia content (in terms of NH3) in the reaction system is 3.5-4.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 800 rpm;

[0215] When the particle size D50 of the solid phase material in the reactor reaches 4.52 μm, the seeding stage ends;

[0216] Growth stage:

[0217] (3) continuously introducing the metal salt solution, NaOH aqueous solution (concentration of 10 mol / L) and ammonia water (concentration of 8 mol / L) into the reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature of 60° C.), wherein the flow rate of the metal salt solution is 30 L / h, the pH value of the reaction system is maintained at 11.0-11.5, the ammonia content (as NH3) in the reaction system is 4.5-5.0 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 600 rpm;

[0218] When the particle size D50 of the solid phase material in the reactor reaches 10.58 μm, the feeding is stopped;

[0219] Post-processing stage:

[0220] (4) The solid phase in the product system obtained in step (3) was separated and washed with water at a washing temperature of 60° C. for 0.5 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as DQ1).

[0221] The D50 of DQ1 is 10.58 μm, the span value is 0.45, and the chemical composition satisfies the chemical formula (Ni 0.80 Co 0.10 Mn 0.10 )(OH)2.

[0222] The SEM test results of DQ1 are as follows: Figure 2 As shown, it can be seen that DQ1 particles have small spheres and medium spheres, and the particle distribution consistency is poor.

[0223] Comparative Preparation Example 2

[0224] Seeding stage:

[0225] (1) In a volume of 1m 3 In a reaction kettle, first add 700 L of pure water, heat to 40°C, then add sodium thiosulfate, NaOH aqueous solution and ammonia water in sequence, stir and mix thoroughly to obtain a reaction base liquid;

[0226] The pH value of the reaction bottom liquid is 12.8, wherein the concentration of sodium thiosulfate is 0.05 g / L, and the content of ammonia (in terms of NH3) is 9.5 / L; the volume of the reaction bottom liquid accounts for 74% of the volume of the reactor;

[0227] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate and cobalt sulfate, wherein the molar ratio of Ni:Co is 90:10 and the total concentration of metal cations is 1.5 mol / L), a NaOH aqueous solution (concentration is 8 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 40° C.), wherein the flow rate of the metal salt solution is 25 L / h, the pH value of the reaction system is maintained at 12.5-13.0, the ammonia (as NH3) content in the reaction system is 9-10 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 700 rpm;

[0228] When the particle size D50 of the solid phase material in the reactor reaches 5.53 μm, the seeding stage ends;

[0229] Growth stage:

[0230] (3) continuously introducing ammonium chloride, the metal salt solution, the NaOH aqueous solution (with a concentration of 8 mol / L) and ammonia water (with a concentration of 8 mol / L) into the above-mentioned reactor, and carrying out a second coprecipitation reaction under a nitrogen atmosphere and stirring conditions (the reaction temperature is 40° C.), wherein the flow rate of the metal salt solution is 25 L / h, the pH value of the reaction system is maintained at 12.0-12.5, the ammonium chloride content in the reaction system is 0.05 mol / L, the ammonia content (as NH3) in the reaction system is 10-11 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 500 rpm;

[0231] When the particle size D50 of the solid phase material in the reactor reaches 13.51 μm, the feeding is stopped;

[0232] Post-processing stage:

[0233] (4) The solid phase in the product system obtained in step (3) is separated and washed with water at a washing temperature of 40° C. for 2 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as DQ2).

[0234] The D50 of DQ2 is 13.51 μm, the span value is 0.40, and the chemical composition satisfies the chemical formula (Ni 0.90 Co 0.10 )(OH)2.

[0235] Comparative Preparation Example 3

[0236] Seeding stage:

[0237] (1) In a volume of 1m 3In a reaction kettle, 500 L of pure water was first added, the temperature was raised to 70°C, and then sodium sulfonate, NaOH and ammonia water (concentration of 8 mol / L) were added in sequence, and the mixture was fully stirred to obtain a reaction base solution;

[0238] The pH value of the reaction bottom liquid is 11.7, wherein the concentration of sodium sulfonate is 0.10 g / L, and the content of ammonia (in terms of NH3) is 8.0 g / L; the volume of the reaction bottom liquid accounts for 52% of the volume of the reactor;

[0239] (2) continuously introducing a metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 40:20:40 and the total concentration of metal cations is 3.0 mol / L), a NaOH aqueous solution (concentration is 5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 70° C.), wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the ammonia (as NH3) content in the reaction system is 7.5-8.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 600 rpm;

[0240] When the particle size D50 of the solid phase material in the reactor reaches 5.94 μm, the seeding stage ends;

[0241] Growth stage:

[0242] (3) continuously introducing the metal salt solution, NaOH aqueous solution (concentration of 5 mol / L) and ammonia water (concentration of 8 mol / L) into the reactor, and conducting a second coprecipitation reaction under nitrogen atmosphere and stirring conditions (reaction temperature of 70° C.), wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 11.0-12.0, the ammonia content (as NH3) in the reaction system is 6.5-7.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 300 rpm;

[0243] When the particle size D50 of the solid phase material in the reactor reaches 12.37 μm, the feeding is stopped;

[0244] Post-processing stage:

[0245] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous ammonium carbonate solution (concentration of 0.12 mol / L) at a washing temperature of 60° C. for 1.8 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as DQ3).

[0246] The D50 of DQ3 is 12.37 μm, the span value is 0.39, and the chemical composition satisfies the chemical formula (Ni0.40 Fe 0.20 Mn 0.40 )(OH)2.

[0247] Comparative Preparation Example 4

[0248] Seeding stage:

[0249] (1) In a volume of 1m 3 In a reaction kettle, 500 L of pure water was first added, the temperature was raised to 70° C., and then sodium sulfonate, NaOH aqueous solution and ammonia water were added in sequence, and the mixture was fully stirred to obtain a reaction bottom liquid;

[0250] The pH value of the reaction bottom liquid is 11.7, wherein the concentration of sodium sulfonate is 0.10 g / L, and the content of ammonia (in terms of NH3) is 8 g / L; the volume of the reaction bottom liquid accounts for 52% of the volume of the reactor;

[0251] (2) continuously introducing a mixed metal salt solution (a mixed aqueous solution of nickel sulfate, iron sulfate and manganese sulfate, wherein the molar ratio of Ni:Fe:Mn is 40:20:40 and the total concentration of metal cations is 3.0 mol / L), a NaOH aqueous solution (concentration is 5 mol / L) and an ammonia solution (concentration is 8 mol / L) into the above-mentioned reactor, and performing a first coprecipitation reaction under a nitrogen atmosphere and stirring conditions (reaction temperature is 70° C.), wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 11.5-12.0, the ammonia content (in terms of NH3) in the reaction system is 7.5-8.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 600 rpm;

[0252] When the particle size D50 of the solid phase material in the reactor reaches 5.88 μm, the seeding stage ends;

[0253] Growth stage:

[0254] (3) continuously introducing ammonium carbonate, the metal salt solution, NaOH aqueous solution (concentration of 5 mol / L) and ammonia water (concentration of 8 mol / L) into the above reactor, and carrying out a second coprecipitation reaction (reaction temperature of 70° C.) under nitrogen atmosphere and stirring conditions, wherein the flow rate of the metal salt solution is 15 L / h, the pH value of the reaction system is maintained at 11.0-12.0, the ammonium carbonate content in the reaction system is 0.15 mol / L, the ammonia content (as NH3) in the reaction system is 6.5-7.5 g / L, the nitrogen flow rate is 500 L / h, and the stirring speed is 300 rpm;

[0255] When the particle size D50 of the solid phase material in the reactor reaches 12.38 μm, the feeding is stopped;

[0256] Post-processing stage:

[0257] (4) The solid phase in the product system obtained in step (3) was separated and washed with an aqueous ammonium carbonate solution (concentration of 0.12 mol / L) at a washing temperature of 60° C. for 1.8 h, followed by drying and sieving to obtain a positive electrode material precursor (denoted as DQ4).

[0258] The D50 of DQ4 is 12.38 μm, the span value is 0.43, and the chemical composition satisfies the chemical formula (Ni 0.40 Fe 0.20 Mn 0.40 )(OH)2.

[0259] Example 1

[0260] Lithium hydroxide and the positive electrode material precursor Q1 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.03:1, and the mixture is sintered at a sintering temperature of 750°C and a sintering time of 14 hours in an oxygen atmosphere to obtain a lithium-ion battery positive electrode material (denoted as L1) after sintering.

[0261] The chemical composition of L1 satisfies the chemical formula Li 1.03 Ni 0.80 Co 0.10 Mn 0.10 O2.

[0262] Example 2

[0263] Lithium hydroxide and the positive electrode material precursor Q2 are uniformly mixed at a molar ratio of Li: (Ni+Co) of 1.01:1, and the mixture is sintered at a sintering temperature of 700°C and a sintering time of 16 hours to obtain a lithium-ion battery positive electrode material (denoted as L2).

[0264] The chemical composition of L2 satisfies the chemical formula Li 1.01 Ni 0.90 Co 0.10 O2.

[0265] Example 3

[0266] Sodium carbonate and the above-mentioned positive electrode material precursor Q3 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.08:1, and the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 8h. Then the temperature is raised to 1000°C for the second sintering for 9h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L3) is obtained.

[0267] The chemical composition of L3 satisfies the chemical formula Na 1.08 Ni 0.40 Fe 0.20 Mn 0.40O2.

[0268] Example 4

[0269] Lithium carbonate and the positive electrode material precursor Q4 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.05:1, and the mixture is sintered at a sintering temperature of 800°C and a sintering time of 12 hours to obtain a lithium-ion battery positive electrode material (denoted as L4) after sintering.

[0270] The chemical composition of L4 satisfies the chemical formula Li 1.05 Ni 0.60 Co 0.20 Mn 0.20 O2.

[0271] Example 5

[0272] Sodium carbonate and the above-mentioned positive electrode material precursor Q5 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn+Zn) of 1.01:1, and the mixture is sintered. The first sintering temperature is 700°C and the sintering time is 6h. Then the temperature is raised to 1100°C for the second sintering for 8h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L5) is obtained.

[0273] The chemical composition of L5 satisfies the chemical formula Na 1.01 Ni 0.32 Fe 0.30 Mn 0.30 Zn 0.08 O2.

[0274] Example 6

[0275] Lithium hydroxide and the positive electrode material precursor Q6 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.1:1, and the mixture is sintered at a sintering temperature of 700°C and a sintering time of 16 hours in an oxygen atmosphere to obtain a lithium-ion battery positive electrode material (denoted as L6).

[0276] The chemical composition of L6 satisfies the chemical formula Li 1.10 Ni 0.95 Co 0.03 Mn 0.02 O2.

[0277] Example 7

[0278] Sodium carbonate and the above-mentioned positive electrode material precursor Q7 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.25:1, and the mixture is sintered. The first sintering temperature is 800°C and the sintering time is 5h. Then the temperature is raised to 1100°C for the second sintering for 8h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L7) is obtained.

[0279] The chemical composition of L7 satisfies the chemical formula Na 1.25 Ni 0.29 Fe 0.30 Mn 0.41 O2.

[0280] Example 8

[0281] Sodium carbonate and the above-mentioned positive electrode material precursor Q8 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.15:1, and the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 2h. Then the temperature is raised to 900°C for the second sintering for 15h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L8) is obtained.

[0282] The chemical composition of L8 satisfies the chemical formula Na 1.15 Ni 0.50 Fe 0.20 Mn 0.30 O2.

[0283] Example 9

[0284] Sodium carbonate and the positive electrode material precursor Q9 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.15:1, and the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 2h. Then the temperature is raised to 900°C for the second sintering for 15h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L9) is obtained.

[0285] The chemical composition of L9 satisfies the chemical formula Na 1.15 Ni 0.50 Fe 0.20 Mn 0.30 O2.

[0286] Example 10

[0287] Sodium carbonate and the above-mentioned positive electrode material precursor Q10 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.15:1, and then the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 2h. Then the temperature is raised to 900°C for the second sintering for 15h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as L10) is obtained.

[0288] The chemical composition of L10 satisfies the chemical formula Na 1.15 Ni 0.50 Fe 0.20 Mn 0.30 O2.

[0289] Comparative Example 1

[0290] Lithium hydroxide and the positive electrode material precursor DQ1 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.03:1, and the mixture is sintered at a sintering temperature of 750°C and a sintering time of 14 hours in an oxygen atmosphere to obtain a lithium-ion battery positive electrode material (denoted as DL1) after sintering.

[0291] The chemical composition of DL1 satisfies the chemical formula Li 1.03 Ni 0.80 Co 0.10 Mn 0.10 O2.

[0292] Comparative Example 2

[0293] Lithium hydroxide and the positive electrode material precursor DQ2 are uniformly mixed at a molar ratio of Li: (Ni+Co+Mn) of 1.01:1, and the mixture is sintered at a sintering temperature of 700°C and a sintering time of 16 hours to obtain a lithium-ion battery positive electrode material (denoted as DL2).

[0294] The chemical composition of DL2 satisfies the chemical formula Li 1.01 Ni 0.90 Co 0.10 O2.

[0295] Comparative Example 3

[0296] Sodium carbonate and the positive electrode material precursor DQ3 are uniformly mixed at a molar ratio of Na: (Ni+Fe+Mn) of 1.08:1, and the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 8 hours. The temperature is then raised to 1000°C for the second sintering for 9 hours. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as DL3) is obtained.

[0297] The chemical composition of DL3 satisfies the chemical formula Na 1.08 Ni 0.40 Fe 0.20 Mn 0.40 O2.

[0298] Comparative Example 4

[0299] Sodium carbonate and the above-mentioned positive electrode material precursor DQ4 are uniformly mixed with a molar ratio of Na: (Ni+Fe+Mn) of 1.08:1 (calculated as metal cations), and then the mixture is sintered. The first sintering temperature is 600°C and the sintering time is 8h. Then the temperature is raised to 1000°C for the second sintering for 9h. The sintering atmosphere is oxygen. After sintering, a sodium ion battery positive electrode material (denoted as DL4) is obtained.

[0300] The chemical composition of DL4 satisfies the chemical formula Na 1.08 Ni0.40 Fe 0.20 Mn 0.40 O2.

[0301] Test Case

[0302] Assemble batteries using the above-mentioned positive electrode materials L1-L10 and DL1-DL4:

[0303] Positive electrode: The positive electrode material (L1-L10, DL1-DL4), conductive agent (Carbon ECP / Super P), binder (PVDF) and dispersant (NMP) are uniformly mixed (wherein the weight ratio of positive electrode material: conductive agent: binder: dispersant is 95:1:2:2) to obtain positive electrode slurry, and the positive electrode slurry is uniformly coated on a clean aluminum foil, and then baked and pressed to obtain a positive electrode sheet;

[0304] Negative electrode: The negative electrode material (graphite), conductive agent (Carbon ECP / Super P), binder (SBR), and thickener (CMC) are weighed in a weight ratio of 95:1:2:2, and mixed evenly in deionized water to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on a clean copper foil, and then baked and pressed to obtain a negative electrode sheet;

[0305] Diaphragm: Celgard PP2075 diaphragm (Celgard, USA);

[0306] Electrolyte: 1 mol / L LiPF6 solution or NaPF6 solution (wherein the solvent is a mixture of EC, PC, EP, and PP in a weight ratio of 1:1:2:6) is used as the electrolyte (Li-ion batteries use LiPF6 solution, and sodium-ion batteries use NaPF6 solution);

[0307] The positive electrode, negative electrode, separator and electrolyte were assembled in sequence to obtain lithium ion batteries or sodium ion batteries (respectively denoted as B1-B10 and DB1-DB4), and charged and discharged at 25°C, voltage of 2.7-4.2V, and 0.2-2.0C rate to test the first discharge specific capacity, first charge and discharge efficiency, and capacity retention rate after 50 cycles. The results are shown in Table 1.

[0308] Table 1

[0309]

[0310]

[0311] As can be seen from Table 1, under the above test conditions, the lithium ion batteries B1-B2 corresponding to Examples 1-2 of the present invention have a higher capacity retention rate after 50 cycles compared with the electrical performance of the lithium ion batteries DB1-DB2 corresponding to Comparative Examples 1-2; the sodium ion battery B3 corresponding to Example 3 of the present invention has a higher capacity retention rate after 50 cycles compared with the electrical performance of the sodium ion batteries DB3-DB4 corresponding to Comparative Examples 3 and 4. This is because the positive electrode material precursor prepared by the method of the present invention has a narrow diameter, a span value between 0.2-0.3, a uniform particle size distribution, no medium or small particles mixed in large particles, and good consistency of the primary particles of the positive electrode material after sintering, which is conducive to the deintercalation of lithium ions or sodium ions, resulting in a significant improvement in cycle stability. In addition, after 50 cycles of the batteries B4-B10 corresponding to Examples 4-10, the capacity retention rates are all above 90%, indicating that the positive electrode material precursor (and positive electrode material) prepared by the method of the present invention can bring good cycle stability.

[0312] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material precursor, characterized in that: The method comprises: (1) preparing a reaction base liquid by mixing raw materials including a first precipitant, a first complexing agent, a first auxiliary agent and water; (2) subjecting the first metal salt solution, the second precipitant, the second complexing agent and the reaction base solution to a first coprecipitation reaction to obtain a first product system containing seed crystals; (3) subjecting a second metal salt solution, a third precipitant, a third complexing agent, a second auxiliary agent and the first product system to a second coprecipitation reaction to obtain a second product system; (4) washing the second product system with a solution containing a third auxiliary agent to obtain a positive electrode material precursor; Wherein, the first auxiliary agent is selected from at least one of A salt, B salt, C salt and D salt; the second auxiliary agent is C salt; the third auxiliary agent is D salt; The A salt is selected from at least one of sulfate, bisulfate and thiosulfate; the B salt is a sulfonate; the C salt is selected from chloride and / or hypochlorite; the D salt is selected from carbonate and / or bicarbonate; The D50 of the positive electrode material precursor is 10-18 μm.

2. The preparation method according to claim 1, wherein The A salt is selected from at least one of sodium sulfate, ammonium sulfate, ammonium bisulfate and sodium thiosulfate; And / or, the B salt is sodium sulfonate; And / or, the C salt is selected from at least one of sodium chloride, ammonium chloride and sodium hypochlorite; And / or, the D salt is selected from at least one of sodium carbonate, sodium bicarbonate, ammonium carbonate and ammonium bicarbonate; And / or, the first auxiliary agent is selected from A salt and / or B salt.

3. The preparation method according to claim 1 or 2, wherein The first precipitant, the second precipitant, and the third precipitant are each independently selected from at least one of sodium hydroxide, sodium carbonate, and sodium bicarbonate; And / or, the first complexing agent, the second complexing agent, and the third complexing agent are ammonia water; And / or, the metal salts in the first metal salt solution and the second metal salt solution are the same, including a metal salt and b metal salt; wherein the a metal salt is a nickel salt, and the b metal salt is selected from a manganese salt and / or a salt containing element M; wherein the element M is selected from at least one of Co, Al, Fe, Zn, Cr, Ti and Mg.

4. The preparation method according to any one of claims 1 to 3, wherein In step (1), the amount of the first precipitant added is such that the pH value of the reaction bottom solution is 10-13; and / or, in the reaction base solution, the concentration of the first complexing agent is 1-12 g / L; and / or, in the reaction base solution, the concentration of the first auxiliary agent is 0.05-0.15 g / L; And / or, the volume of the reaction base liquid accounts for 50-80% of the volume of the reaction kettle used for the coprecipitation reaction.

5. The preparation method according to any one of claims 1 to 4, wherein: In step (2), the conditions of the first coprecipitation reaction include: a temperature of 40-80° C., a pH value of the reaction system of 10-13, and a concentration of the complexing agent in the reaction system of 1-12 g / L; and / or, the concentration of the metal salt in the first metal salt solution is 1-3 mol / L, and the volume flow rate per hour is 1-10% of the volume of the reactor used for the coprecipitation reaction; And / or, the second precipitant and the second complexing agent are each fed in the form of an aqueous solution; wherein the concentration of the aqueous solution of the second precipitant is 5-11 mol / L; the concentration of the aqueous solution of the second complexing agent is 6-10 mol / L; And / or, the feeding flow rate of the second precipitant is such that the pH value of the reaction system is maintained at 10-13; the feeding flow rate of the second complexing agent is such that the concentration of the complexing agent in the reaction system is maintained at 1-12 g / L; And / or, the seed crystal has a D50 of 1-6 μm.

6. The preparation method according to any one of claims 1 to 5, wherein: In step (3), the conditions of the second coprecipitation reaction include: a temperature of 40-80° C., a pH value of the reaction system of 10-13, and a concentration of the complexing agent in the reaction system of 1-12 g / L; and / or, the concentration of the metal salt in the second metal salt solution is 1-3 mol / L, and the volume flow rate per hour is 1-10% of the volume of the reactor used for the coprecipitation reaction; and / or, the feeding amount of the second auxiliary agent is such that the concentration of the second auxiliary agent in the reaction system is 0.02-0.15 g / L; And / or, the third precipitant and the third complexing agent are each fed in the form of an aqueous solution; wherein the concentration of the aqueous solution of the third precipitant is 5-11 mol / L; the concentration of the aqueous solution of the third complexing agent is 6-10 mol / L; And / or, the feeding flow rate of the third precipitant is such that the pH value of the reaction system is maintained at 10-13; the feeding flow rate of the third complexing agent is such that the concentration of the complexing agent in the reaction system is maintained at 1-12 g / L.

7. The preparation method according to any one of claims 1 to 6, wherein: In step (4), in the solution containing the third auxiliary agent, the concentration of the third auxiliary agent is 0.05-0.2 mol / L; And / or, the washing conditions include: temperature of 40-60° C. and time of 0.5-2 h.

8. A cathode material precursor obtained by the method according to any one of claims 1 to 7.

9. A positive electrode material, characterized in that: The positive electrode material is prepared by sintering the positive electrode material precursor according to claim 8 and a lithium source or a sodium source.

10. A battery comprising the positive electrode material according to claim 9.